The Impact Of Physical Environment Of Bank Services In Its Customer Satisfaction Field Study At Syrian Commercial And Real Estate Bank - ناصر, سومر (Latakia University Journal - Economic and Legal Sciences Series, 2020)
This research aimed to study some factors that affect the physical environment of bank services and its effect customer satisfaction regarding the services provided. The most important results were as follows: ATMs present performance was not up to the acceptable level. Computers performance was no up to the acceptable level. Places for providing bank services are satisfactory. The most important conclusion could be represented as the follows: It would be necessary to improve ATMs and computers and other electronic machines (printers, calculators, and scanners) in commercial and real estate banks. It would be necessary to increase ATMs number in commercial and real estate banks. It would be necessary to repair ATMs and computers and other electronic machines(printers, calculators) in commercial and real estate banks. It would be necessary to establish a maintenance team.